2016
DOI: 10.1086/686223
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Replication of the Effects of a Supplementary, Technology-Assisted, Storybook Intervention for Preschool Children with Weak Vocabulary and Comprehension Skills

Abstract: In 2013, Spencer, Goldstein, Sherman, et al. reported the promising effects of a supplemental, technology-assisted, storybook intervention (Tier 2) containing embedded instruction targeting the oral language learning of preschool children at risk for delays. We sought to advance knowledge of the intervention by replicating it in a new sample and examining children's responses to the narrator's instructional prompts and associations with learning outcomes. Results indicated that children were highly successful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 46 publications
(74 reference statements)
0
34
0
2
Order By: Relevance
“…Learning of vocabulary words and question answering was assessed at approximately monthly intervals. Goldstein et al (2016) found large, significant group differences in favor of the treatment group for learning target vocabulary words but no significant group differences for the question-answering outcome. Participants in the Story Friends treatment gained an average of 3.4 word points per unit, with large effect sizes of 0.70 (Cohen's f 2 ) relative to the comparison group.…”
Section: Story Friends Programmentioning
confidence: 69%
See 4 more Smart Citations
“…Learning of vocabulary words and question answering was assessed at approximately monthly intervals. Goldstein et al (2016) found large, significant group differences in favor of the treatment group for learning target vocabulary words but no significant group differences for the question-answering outcome. Participants in the Story Friends treatment gained an average of 3.4 word points per unit, with large effect sizes of 0.70 (Cohen's f 2 ) relative to the comparison group.…”
Section: Story Friends Programmentioning
confidence: 69%
“…The current investigation is a secondary examination of data from the efficacy study of Story Friends conducted by Goldstein et al (2016). Details of the study, including specifics of the Story Friends program, are reported there.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations